Study of patients with peritonitis admitted to the National Center for Minimal Access Surgery - Lilian Valdivia García; Maricela Morera Pérez (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Postoperative peritonitis is one of the most frequent complications that occurs after laparoscopic procedures. Objective: To characterize the evolution of patients complicated by peritonitis after a laparoscopic procedure. Material and method: An observational descriptive study was conducted in patients with peritonitis who were admitted to the Intensive Care Unit of the National Center for Minimal Access Surgery from September 2010 to December 2015. Some variables were analyzed such as demographic ones, laparoscopic procedures which were complicated with this diagnosis, clinical complications, antibiotic therapy used, type of nutrition, and physiology and chronic health evaluation (APACHE II) scoring for predicting prognosis. The information was acquired from clinical histories. Qualitative variables were summarized using absolute frequencies and percentages; mean and standard deviation were used for the quantitative ones. Results: 26 out of the 298 patients admitted during the study period complicated by peritonitis (8,7%), the average age was 60 years, and the female sex predominated in the study (57,7%). The most complicated patients with this diagnosis were the ones with perforation following colonoscopy (50,0%). Electrolyte imbalance (73,1%) was the most frequent associated complication. Early enteral nutrition was used in 57,7% of the cases; and the most used antibiotics were Ceftriaxone, Amikacin, and Metronidazole. The favorable evolution predominated despite the APACHE II score remained high. Conclusions: Intestinal perforations following a colonoscopy have a high risk of suffering from secondary peritonitis, but its evolution is favorable if an early diagnosis and treatment is established. Keywords: peritonitis, intra-abdominal sepsis, postoperative complications, endoscopic procedures, antibiotic therapy, postoperative mortality.